К экологии домового воробья в условиях города - Бондаревская, Е.Ф. (Вестник зоологии, 1968)
House sparrow, in spite of some data of the literature, remain one of the flourishing species of birds with synanthropic mode of life. According to the observations in Poltava and towns of the Poltava region in winter this species feeds near granaries, shops and enterprises, in spring and autumn they live on the account of insects of trees and shrubbery plantations. Thus the house sparrow is a noticealbe factor regulating a number of plants in towns.